Antimicrobial prescription patterns in a tertiary-care pediatric unit in Thailand - Sineenart Chautrakarn (2020)
© 2020 Japan Pediatric Society Background: Antimicrobial resistance is one of the greatest public health threats worldwide. The improper prescription of antibiotics is one factor that promotes antibiotic resistance. Access to antimicrobial surveillance data is essential when assessing the pattern and appropriateness of antimicrobial prescriptions in hospitals and for the establishment of an antimicrobial stewardship program. This study aimed to describe the rate of antimicrobial use and the pattern of prescriptions in a tertiary care pediatric unit in Thailand. Methods: A point prevalence survey on antimicrobial use was conducted monthly between January and June 2016, using standardized tools. The survey included all inpatient pediatric beds and identified all children receiving antimicrobial treatment on the day of the survey. Results: The study included 644 children, 43.3% of whom received antimicrobial treatment during hospitalization. In general wards, the rate of antimicrobial prescriptions was 37.2%; in oncology wards it was 47.0%; in intensive care units it was 38.7%, and in surgical wards it was 67.7%. Meropenem was the most prescribed antimicrobial in the general wards (24.5%) and intensive care units (28.6%), whereas antipseudomonas was the most commonly prescribed antimicrobial in the oncology ward (26.6%). For the surgical ward, the most prescribed antimicrobial was third-generation cephalosporin for both prophylaxis and treatment (39.0%). The most common reason for antimicrobial use was the treatment of infections. Conclusions: Nearly half of hospitalized children received at least one antimicrobial. This was comparable with other pediatric tertiary care centers, although the high use of meropenem was different. This study provides important baseline information on antimicrobial use in a large tertiary-care pediatric unit and could lead to a nationwide survey in the future.